Battery positive electrode material, preparation method thereof and battery composed of battery positive electrode material
By forming a conformal cladding layer on the surface of manganese dioxide nanowires, the structural collapse and conductivity problems of manganese dioxide nanowires in aqueous zinc ion batteries are solved, and the structural stability and conductivity of the material are improved.
Patent Information
- Application Number
- CN202411649317.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-18
AI Technical Summary
When used as the positive electrode material of aqueous zinc ion batteries, manganese dioxide nanowires have structural collapse and poor conductivity problems. The existing modification solutions are complex and the effects are difficult to achieve expectations.
Manganese dioxide itself acts as an oxidant to initiate polymer polymer polymer on the surface of manganese dioxide nanowires, forming a conformal coating layer to improve the structural stability and conductivity of the material.
The structural stability and conductivity of manganese dioxide nanowires are achieved while improving the cyclic stability and rate performance of the material.
Smart Images

Figure CN119581514A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery materials and relates to a battery positive electrode material and a preparation method thereof and a battery composed thereof. Background Art
[0002] Aqueous zinc-ion batteries have attracted widespread attention due to their environmental friendliness, high safety, and low price. Manganese dioxide is the most studied positive electrode material with large-scale application prospects because of its advantages such as high specific capacity, high voltage platform, and abundant reserves. Different properties can be given to materials by preparing different structural morphologies. Among them, manganese dioxide nanowires have the advantages of one-dimensional structural metal oxide materials, with unique characteristics such as large surface area, abundant active sites, and fast ion diffusion. However, when used as positive electrode materials for aqueous zinc-ion batteries, manganese dioxide nanowires still face serious problems of structural collapse and poor conductivity, which hinders the further development of manganese dioxide nanowires.
[0003] In response to the above problems, the solutions currently proposed include conductive material coating, ion doping, and constructing oxygen vacancies, but these solutions can only solve one aspect of the problem. For example, conductive material coating can improve the structural stability of the material and the conductivity of the outer layer, but the conductivity of the inner layer of the material cannot be improved at the same time. Ion doping can improve the structural stability of the material, but it cannot improve the conductivity of the material. Oxygen vacancies can improve the conductivity inside the material, but are poor in terms of structural stability. Therefore, in order to simultaneously improve the stability of the material structure and the conductivity inside and outside the material, it is necessary to combine two or more solutions for modification, which will cause the operation steps to be too cumbersome and cannot be achieved in one step. In addition, the controllability of the intermediate process is reduced, which will damage the intrinsic structure of the manganese dioxide nanowires, and the modification effect is difficult to achieve the expected effect. Summary of the invention
[0004] The present invention aims to provide a positive electrode material for a battery, a preparation method thereof and a battery composed of the materials. Manganese dioxide itself is used as an oxidant to initiate a polymerization reaction of a conductive polymer on the surface of a manganese dioxide nanowire. A conformal coating layer is formed on the surface of the manganese dioxide nanowire through a one-step reaction, which can reduce the self-polymerization products of the conductive polymer. The binding force between the conformal coating layer and the manganese dioxide nanowire is stronger. Manganese dioxide itself is used as an oxidant to initiate self-initiation without adding an additional oxidant. The reaction conditions are mild, which ensures the initial nanowire morphology of the manganese dioxide nanowire. The coated conductive polymer layer can effectively stabilize the structure of the manganese dioxide nanowire, thereby ensuring the conductivity of the inner layer manganese dioxide nanowire and improving the cycle stability of the manganese dioxide nanowire coated with the conductive polymer. At the same time, the conformal coating of the conductive polymer realizes the introduction of oxygen vacancies. The introduction of oxygen vacancies can improve the transmission of electrons in the manganese dioxide nanowire coated with the conductive polymer. On the basis of improving the conductivity of the conductive polymer, the conductivity of the manganese dioxide nanowire coated with the conductive polymer is further improved.
[0005] In a first aspect, the present invention provides a positive electrode material for a battery, comprising manganese dioxide nanowires and a conductive polymer, wherein the conductive polymer is coated on the surface of the manganese dioxide nanowires.
[0006] The conductive polymer and manganese dioxide nanowires themselves have high conductivity respectively. Coating the conductive polymer on the surface of the manganese dioxide nanowires ensures the initial nanowire morphology of the manganese dioxide nanowires. The coated conductive polymer layer can effectively stabilize the structure of the manganese dioxide nanowires, thereby ensuring the conductivity of the inner layer manganese dioxide nanowires. The combination of the two structures further improves the conductivity and stability of the manganese dioxide nanowires coated with the conductive polymer.
[0007] In some embodiments, the battery cathode material has oxygen vacancies.
[0008] The conformal coating of the conductive polymer realizes the introduction of oxygen vacancies. The introduction of oxygen vacancies can improve the transmission of electrons in the manganese dioxide nanowires coated with the conductive polymer. On the basis of improving the conductivity of the conductive polymer, the conductivity of the manganese dioxide nanowires coated with the conductive polymer is further improved, thereby improving the rate performance of the manganese dioxide nanowires coated with the conductive polymer.
[0009] In some embodiments, the conductive polymer includes at least one of a 3,4-ethylenedioxythiophene polymer, a pyrrole polymer, and an aniline polymer.
[0010] 3,4-ethylenedioxythiophene polymer, pyrrole polymer, and aniline polymer are used as coating layers of positive electrode materials. They not only have excellent conductivity themselves, but also have stronger binding force with manganese dioxide nanowires. They can effectively stabilize the structure of manganese dioxide nanowires, make it easier to introduce oxygen vacancies, improve the transmission of electrons in manganese dioxide nanowires coated with conductive polymers, and improve the conductivity of manganese dioxide nanowires coated with conductive polymers.
[0011] In some embodiments, the manganese dioxide nanowires are prepared by hydrothermal reaction of ammonium sulfate, manganese sulfate and ammonium persulfate;
[0012] Preferably, the molar ratio of ammonium sulfate, manganese sulfate and ammonium persulfate is 3-5:0.5-1.5:1;
[0013] Preferably, the temperature of the hydrothermal reaction is 150-200° C., and the time of the hydrothermal reaction is 20-30 h.
[0014] The prepared manganese dioxide nanowire has a more stable structure and better conductivity. The battery prepared by using the prepared manganese dioxide nanowire as the positive electrode has good specific capacity and stability.
[0015] In a second aspect of the present invention, there is provided a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0016] The manganese dioxide nanowires are added into a dispersion solvent, the pH range is adjusted, a polymer monomer is added and mixed, and a polymerization reaction is carried out to obtain the manganese dioxide nanowires coated with a positive electrode material polymer.
[0017] Adding manganese dioxide nanowires to a dispersing solvent makes it easier to mix the manganese dioxide nanowires with polymer monomers, and using manganese dioxide itself as an oxidant to initiate a polymerization reaction of the conductive polymer on the surface of the manganese dioxide nanowires. A conformal coating layer is formed on the surface of the manganese dioxide nanowires through a one-step reaction, which can reduce the self-polymerization products of the conductive polymer. The conformal coating layer has a stronger binding force with the manganese dioxide nanowires. Manganese dioxide itself acts as an oxidant to self-initiate without adding additional oxidants. The reaction conditions are mild, which ensures the initial nanowire morphology of the manganese dioxide nanowires. The coated conductive polymer layer can effectively stabilize the structure of the manganese dioxide nanowires, thereby ensuring the conductivity of the inner layer manganese dioxide nanowires. The prepared manganese dioxide nanowires have a more stable structure and better conductivity.
[0018] In some embodiments, the pH range is 2.5-4.5;
[0019] Preferably, the pH range is 3-4
[0020] The pH of the polymerization reaction will also affect the structure of the manganese dioxide nanowires coated with the conductive polymer, thereby affecting its conductivity. It was finally found that the manganese dioxide nanowires coated with the conductive polymer prepared when the pH of the polymerization reaction was in the range of 3-4 had higher specific capacity and stability.
[0021] In some embodiments, the manganese dioxide nanowires and the polymer monomers are mixed at a mass ratio of 0.5-2.5:1;
[0022] Preferably, the manganese dioxide nanowires and the polymer monomers are mixed in a mass ratio of 1-2:1; the polymer monomers include at least one of 3,4-ethylenedioxythiophene monomers, pyrrole monomers, and aniline monomers.
[0023] When the ratio of manganese dioxide nanowires to the polymer monomer is within this range, the coating layer can not only completely and evenly coat the manganese dioxide nanowires, but also maximize the conductivity. When the conductive polymer monomer is too little, such as when the mass ratio of the conductive polymer monomer to the manganese dioxide nanowire is less than 0.5, the conductivity and rate performance of the manganese dioxide nanowire coated with the conductive polymer are both low due to the small amount of conductive polymer layer coated on the surface of the manganese dioxide nanowire. When the conductive polymer monomer is too much, such as when the mass ratio of the conductive polymer monomer to the manganese dioxide nanowire is greater than 2.5, the battery specific capacity and capacity retention rate composed of the obtained manganese dioxide nanowire positive electrode material coated with the conductive polymer are reduced instead.
[0024] 3,4-ethylenedioxythiophene polymers, pyrrole polymers, and aniline polymers themselves have excellent electrical conductivity, and have stronger binding force with manganese dioxide nanowires, which can effectively stabilize the structure of manganese dioxide nanowires, make it easier to introduce oxygen vacancies, improve the transmission of electrons in manganese dioxide nanowires coated with conductive polymers, and improve the conductivity of manganese dioxide nanowires coated with conductive polymers.
[0025] In some embodiments, the manganese dioxide nanowires are prepared by hydrothermal reaction of ammonium sulfate, manganese sulfate and ammonium persulfate;
[0026] Preferably, the molar ratio of ammonium sulfate, manganese sulfate and ammonium persulfate is 3-5:0.5-1.5:1;
[0027] Preferably, the temperature of the hydrothermal reaction is 150-200° C., and the time of the hydrothermal reaction is 20-30 h.
[0028] When the molar ratio of ammonium sulfate, manganese sulfate and ammonium persulfate is 3-5:0.5-1.5:1 and the reaction temperature is within the range of 150-200° C., the battery prepared by using the prepared manganese dioxide nanowires as the positive electrode has good specific capacity and stability.
[0029] According to a third aspect of the present invention, a battery is provided, comprising any one of the above-mentioned positive electrode materials.
[0030] Since the conductive polymer and manganese dioxide nanowires in the positive electrode material have high conductivity respectively, the coated conductive polymer layer can effectively stabilize the structure of the manganese dioxide nanowires and ensure the conductivity of the inner layer manganese dioxide nanowires. The combination of the two structures further improves the conductivity and stability of the manganese dioxide nanowires coated with the conductive polymer. The battery prepared using this positive electrode material has higher specific capacity and stability.
[0031] A fourth aspect of the present invention provides a method for preparing a battery, comprising the following steps:
[0032] S1. Prepare a positive electrode for a battery: add the positive electrode material for a battery according to any one of claims 1 to 4 or the positive electrode material prepared by the preparation method according to any one of claims 5 to 8 to N-methylpyrrolidone, mix into a uniform slurry, and coat the slurry on a titanium foil to prepare a positive electrode for a zinc ion battery;
[0033] S2. Prepare the battery: Use metal zinc sheet as the negative electrode, glass fiber as the separator, and zinc sulfate as the electrolyte to assemble into a button battery;
[0034] Preferably, the mass ratio of the positive electrode material, acetylene black and polyvinylidene fluoride is 5-10:0.5-2:1;
[0035] Preferably, the solid content of the slurry is 55% to 60%.
[0036] When the mass ratio of positive electrode material, acetylene black and polyvinylidene fluoride is 5-10:0.5-2:1 and the solid content of the slurry is 55% to 60%, the ratio of positive electrode material to N-methylpyrrolidone can be ensured, and the obtained battery has higher specific capacity and stability.
[0037] In summary, the present application includes at least one of the following beneficial technical effects:
[0038] The conductive polymer and manganese dioxide nanowires themselves have high conductivity respectively. Coating the conductive polymer on the surface of the manganese dioxide nanowires ensures the initial nanowire morphology of the manganese dioxide nanowires. The coated conductive polymer layer can effectively stabilize the structure of the manganese dioxide nanowires, thereby ensuring the conductivity of the inner layer manganese dioxide nanowires. The combination of the two structures further improves the conductivity and stability of the manganese dioxide nanowires coated with the conductive polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is a SEM image of the PEDOT-coated manganese dioxide nanowires in Example 1;
[0040] Figure 2 The Raman spectra of manganese dioxide, PEDOT, and PEDOT-coated manganese dioxide in Example 5;
[0041] Figure 3 The electron paramagnetic resonance (EPR) spectra of manganese dioxide and PEDOT-coated manganese dioxide nanowires in Example 5;
[0042] Figure 4 The figure is a rate performance curve diagram of the batteries in Example 5 and Comparative Example 1 at different current densities;
[0043] Figure 5 The graph is a cycle performance curve of the batteries in Example 5 and Comparative Example 1 after 500 cycles at a current density of 0.4 A / g. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below by specific embodiments, which do not limit the protection scope of the present invention. Some non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the protection scope of the present invention.
[0045] At present, when manganese dioxide nanowires are used as positive electrode materials for aqueous zinc ion batteries, there are serious problems of structural collapse and poor electrical conductivity. Solutions to the problem include conductive material coating, ion doping, and construction of oxygen vacancies, but the above solutions can only solve one aspect of the problem. For example, conductive material coating can improve the structural stability of the material and the electrical conductivity of the outer layer, but the electrical conductivity of the inner layer of the material cannot be improved at the same time. Ion doping can improve the structural stability of the material, but it cannot improve the electrical conductivity of the material. Oxygen vacancies can improve the electrical conductivity inside the material, but are poor in terms of structural stability of the material. Therefore, in order to simultaneously improve the stability of the material structure and the electrical conductivity inside and outside the material, it is necessary to combine two or more schemes for modification, resulting in the operation steps being too cumbersome and unable to be achieved in one step, and the controllability of the intermediate process is reduced, which will damage the intrinsic structure of the manganese dioxide nanowires, and the modification effect is also difficult to achieve the expected effect.
[0046] Based on this, we tried to prepare a new positive electrode material. Since manganese dioxide nanowires have a large specific surface area and abundant active sites, they can increase the reaction area between the material and zinc ions. Manganese dioxide nanowires can improve the overall specific capacity. Therefore, manganese dioxide nanowires were selected as the basic material.
[0047] We tried to combine different materials with manganese dioxide nanowires, and finally found that the manganese dioxide nanowires coated with conductive polymers as coating materials coated on the surface of manganese dioxide nanowires not only have excellent conductivity in both the inner and outer layers, but also have a stable structure, high cycle stability and rate performance. In the preparation process, a layer of conductive structure can be coated on the surface of manganese dioxide nanowires through a one-step reaction. After further analysis, it was determined that the internal structure of the obtained material is still manganese dioxide nanomaterials, so the inner layer has a higher conductivity. The structure of the outer coating layer was analyzed to be mainly the product of the polymerization reaction of conductive polymer monomers, which has high conductivity and stability. At the same time, many oxygen vacancies were found in this structural layer.
[0048] Through the analysis of the results, manganese dioxide itself acts as an oxidant to initiate the polymerization reaction of the conductive polymer monomer on the surface of the manganese dioxide nanowires. A conformal coating layer is formed on the surface of the manganese dioxide nanowires through a one-step reaction, which can reduce the self-polymerization products of the conductive polymer in the solution. The addition of additional oxidants will lead to the formation of more self-polymerized conductive polymers in the solution, affecting the coating effect of the conductive polymer layer on the surface of manganese dioxide. Conductive polymers can only polymerize on the surface of manganese dioxide nanowires to form a conformal coating layer. The conformal coating layer has a stronger binding force with the manganese dioxide nanowires. Manganese dioxide itself acts as an oxidant to initiate self-initiation without the need to add additional oxidants. The reaction conditions are mild, ensuring the initial nanowire morphology of the manganese dioxide nanowires. The coated conductive polymer layer can effectively stabilize the structure of the manganese dioxide nanowires, thereby ensuring the conductivity of the inner layer of the manganese dioxide nanowires and improving the cyclic stability of the manganese dioxide nanowires coated with conductive polymers. At the same time, the conductive polymer can also improve the electronic conductivity of the manganese dioxide nanowires.
[0049] In addition, conformal coating of the conductive polymer realizes the introduction of oxygen vacancies, which can improve the transmission of electrons in the manganese dioxide nanowires coated with the conductive polymer. On the basis of improving the conductivity of the conductive polymer, the conductivity of the manganese dioxide nanowires coated with the conductive polymer is further improved, thereby improving the rate performance of the manganese dioxide nanowires coated with the conductive polymer.
[0050] Furthermore, in the process of preparing manganese dioxide nanowires, we found that not any conductive polymer coated on the surface of manganese dioxide nanowires can achieve the above-mentioned effect. The conductive polymers that can achieve the above-mentioned effect mainly include 3,4-ethylenedioxythiophene monomer, pyrrole monomer, and aniline monomer. Among them, the manganese dioxide nanowires coated with conductive polymers prepared with 3,4-ethylenedioxythiophene monomer as the conductive polymer monomer are used as the positive electrode of the battery. Not only does it have a higher specific capacity at different current densities, but also the capacity retention rate is the highest.
[0051] The addition ratio of the conductive polymer monomer to the manganese dioxide nanowire is not an arbitrary ratio. When the conductive polymer monomer is too little, such as the mass ratio of the conductive polymer monomer to the manganese dioxide nanowire is less than 0.5, the conductivity and rate performance of the manganese dioxide nanowire coated with the conductive polymer are low due to the small amount of conductive polymer layer coated on the surface of the manganese dioxide nanowire. When the conductive polymer monomer is too much, such as the mass ratio of the conductive polymer monomer to the manganese dioxide nanowire is greater than 2.5, the specific capacity and capacity retention rate of the battery composed of the positive electrode material of the manganese dioxide nanowire coated with the obtained conductive polymer are reduced. At the same time, the pH of the polymerization reaction will also affect the structure of the manganese dioxide nanowire coated with the conductive polymer, thereby affecting its conductivity. It was finally found that the manganese dioxide nanowire coated with the conductive polymer obtained when the pH of the polymerization reaction is in the range of 3-4 has a higher specific capacity and stability.
[0052] At the same time, the raw material ratio, temperature and time of the hydrothermal reaction were also adjusted during the experiment. When the molar ratio of ammonium sulfate, manganese sulfate and ammonium persulfate was 3-5:0.5-1.5:1 and the reaction temperature was in the range of 150-200°C, the battery made with the obtained manganese dioxide nanowires as the positive electrode had good specific capacity and stability.
[0053] Example 1
[0054] A method for preparing a positive electrode material, wherein the positive electrode material is manganese dioxide nanowires coated with a conductive polymer, comprising the following steps:
[0055] 1. Preparation of manganese dioxide nanowires
[0056] Ammonium sulfate, manganese sulfate and ammonium persulfate were added to 200 mL of deionized water, stirred until completely dissolved, and then transferred to a high-temperature reactor for hydrothermal reaction. At the same time, magnetic stirring was applied to the reaction solution. After the reaction was completed, centrifugation and drying were performed to obtain manganese dioxide nanowires.
[0057] In some embodiments, the molar ratio of ammonium sulfate, manganese sulfate and ammonium persulfate is 3-5:0.5-1.5:1, such as 3:0.5:1, 4:1:1, 4:1.5:1, 5:0.5:1, etc.
[0058] In some embodiments, the temperature of the hydrothermal reaction is 150-200°C, and the time of the hydrothermal reaction is 20-30h, such as the temperature of the hydrothermal reaction is 150°C, the time of the hydrothermal reaction is 30h, the temperature of the hydrothermal reaction is 160°C, the time of the hydrothermal reaction is 28h, etc.
[0059] In some embodiments, 20 mmol of ammonium sulfate, 5 mmol of manganese sulfate, and 5 mmol of ammonium persulfate are added to 200 mL of deionized water, stirred until completely dissolved, and then transferred to a high-temperature reactor for hydrothermal reaction at 180°C for 24 hours. At the same time, magnetic stirring is applied to the reaction solution. After the reaction is completed, centrifugation and drying are performed to obtain manganese dioxide nanowires.
[0060] 2. Preparation of positive electrode materials, manganese dioxide nanowires coated with conductive polymers
[0061] The manganese dioxide nanowires are added into a dispersion solvent, the pH range is adjusted, a polymer monomer is added and mixed, and a polymerization reaction is carried out to obtain the manganese dioxide nanowires coated with a positive electrode material polymer.
[0062] In some embodiments, the pH is adjusted to a range of 2.5-4.5, such as pH 2.5, pH 3, pH 3.5, pH 4.5, etc.
[0063] In some embodiments, the mixed mass of manganese dioxide nanowires and the polymer monomers is 0.5-2.5:1, for example, the mixed mass of manganese dioxide nanowires and the polymer monomers is 0.5:1, the mixed mass of manganese dioxide nanowires and the polymer monomers is 1:1, the mixed mass of manganese dioxide nanowires and the polymer monomers is 2:1, the mixed mass of manganese dioxide nanowires and the polymer monomers is 2.5:1, etc.
[0064] In some embodiments, the polymer monomer includes at least one of 3,4-ethylenedioxythiophene monomer, pyrrole monomer, and aniline monomer, such as the polymer monomer is one of 3,4-ethylenedioxythiophene monomer, pyrrole monomer, or aniline monomer; the polymer monomer is a mixture of 3,4-ethylenedioxythiophene monomer, pyrrole monomer, and aniline monomer; the polymer monomer is a mixture of 3,4-ethylenedioxythiophene monomer and pyrrole monomer; the polymer monomer is a mixture of 3,4-ethylenedioxythiophene monomer and aniline monomer; the polymer monomer is a mixture of pyrrole monomer and aniline monomer, etc.
[0065] In some embodiments, the dispersant is deionized water or pure water.
[0066] In some embodiments, 1.0 g of the manganese dioxide nanowires prepared in step 1 is weighed and added to 500 mL of deionized water, ultrasonically dispersed, continuously stirred, an appropriate amount of dilute hydrochloric acid is added to adjust the pH of the mixture to between 3 and 4, 0.5 g of a conductive polymer monomer 3,4-ethylenedioxythiophene monomer is added, ultrasonically dispersed, stirred at high speed, and polymerized for 12 h, centrifuged, and freeze-dried to obtain PEDOT-coated manganese dioxide nanowires (0 v-MnO2@PEDOT), and the obtained PEDOT-coated manganese dioxide nanowires are rich in oxygen vacancies.
[0067] Example 2
[0068] A positive electrode material, a method for preparing manganese dioxide nanowires coated with a conductive polymer, which is different from Example 1 in that in the step of preparing the manganese dioxide nanowires coated with a conductive polymer, the conductive polymer monomer is a pyrrole monomer.
[0069] Example 3
[0070] A positive electrode material, a method for preparing manganese dioxide nanowires coated with a conductive polymer, which is different from Example 1 in that in the step of preparing the manganese dioxide nanowires coated with a conductive polymer, the conductive polymer monomer is an aniline monomer.
[0071] Example 4
[0072] A positive electrode material, a method for preparing manganese dioxide nanowires coated with a conductive polymer, which is different from Example 1 in that in the step of preparing the manganese dioxide nanowires coated with a conductive polymer, the added amount of the conductive polymer monomer 3,4-ethylenedioxythiophene monomer is 1.0 g.
[0073] Example 5
[0074] A method for preparing a button battery comprises the following steps:
[0075] S1. Preparation of battery positive electrode
[0076] The PEDOT-coated manganese dioxide nanowires prepared in Example 1 were added into N-methylpyrrolidone as a positive electrode material, mixed into a uniform slurry, and the slurry was coated on a titanium foil to prepare a positive electrode for a zinc ion battery.
[0077] In some embodiments, the mass ratio of the positive electrode material, acetylene black, and polyvinylidene fluoride is 5-10:0.5-2:1, such as the mass ratio of the positive electrode material, acetylene black, and polyvinylidene fluoride is 5:0.5:1, the mass ratio of the positive electrode material, acetylene black, and polyvinylidene fluoride is 8:1:1, the mass ratio of the positive electrode material, acetylene black, and polyvinylidene fluoride is 10:1.5:1, etc.
[0078] In some embodiments, the solid content of the slurry is 55% to 60%, such as the solid content of the slurry is 55%, 56%, 57%, 58%, 59%, 60%, etc.
[0079] In some embodiments, the PEDOT-coated manganese dioxide nanowires rich in oxygen vacancies prepared in Example 1 are used as active materials, and are added to N-methylpyrrolidone in a mass ratio of 8:1:1 among active materials, acetylene black, and polyvinylidene fluoride, and mixed into a uniform slurry, the solid content of the slurry is controlled at 55%, and the slurry is coated on a titanium foil to prepare a positive electrode for a zinc ion battery;
[0080] S2. Preparation of batteries
[0081] A CR2025 button battery is assembled using a metal zinc sheet as the negative electrode, glass fiber as the separator, and zinc sulfate as the electrolyte.
[0082] Example 6
[0083] A method for preparing a button battery comprises the following steps:
[0084] S1. Preparing a positive electrode for a battery: using the polypyrrole-coated manganese dioxide nanowires prepared in Example 2 as an active material, adding the active material, acetylene black, and polyvinylidene fluoride in a mass ratio of 8:1:1 into N-methylpyrrolidone, mixing and grinding to form a uniform slurry, wherein the solid content of the slurry is controlled at 55% to 60%, and coating the slurry on a titanium foil to prepare a positive electrode for a zinc ion battery;
[0085] S2. Prepare the battery: Use metal zinc sheet as the negative electrode, glass fiber as the separator, and zinc sulfate as the electrolyte to assemble into a CR2025 button battery.
[0086] Example 7
[0087] A method for preparing a button battery comprises the following steps:
[0088] S1. Preparation of a positive electrode for a battery: The polyaniline-coated manganese dioxide nanowires prepared in Example 3 are used as an active material, and are added into N-methylpyrrolidone in a mass ratio of 8:1:1 among the active material, acetylene black and polyvinylidene fluoride, and mixed and ground into a uniform slurry, wherein the solid content of the slurry is controlled at 55% to 60%, and the slurry is coated on a titanium foil to prepare a positive electrode for a zinc ion battery;
[0089] S2. Prepare the battery: Use metal zinc sheet as the negative electrode, glass fiber as the separator, and zinc sulfate as the electrolyte to assemble into a CR2025 button battery.
[0090] Example 8
[0091] A method for preparing a button battery comprises the following steps:
[0092] S1. Preparation of a positive electrode for a battery: The PEDOT-coated manganese dioxide nanowires rich in oxygen vacancies prepared in Example 4 are used as an active material, and are added into N-methylpyrrolidone in a mass ratio of 8:1:1 of the active material, acetylene black, and polyvinylidene fluoride, and mixed and ground into a uniform slurry, wherein the solid content of the slurry is controlled at 55% to 60%, and the slurry is coated on a titanium foil to prepare a positive electrode for a zinc ion battery;
[0093] S2. Prepare the battery: Use metal zinc sheet as the negative electrode, glass fiber as the separator, and zinc sulfate as the electrolyte to assemble into a CR2025 button battery.
[0094] Performance Testing
[0095] 1. The button cells prepared in Examples 5-8 were subjected to the following performance tests:
[0096] (1) Test the rate performance at different current densities. The specific test method is to clamp the button battery to the Xinwei battery tester, detect that the battery is normal and has no short circuit, and then set the parameters on the BTS client on the control computer. The set parameters include the mass of the active material, the tested current density of 0.1, 0.2, 0.4, 0.8, 1.0, 1.5, 2.0, 3.0, 5.0A / g, the charge cut-off voltage of 1.8V, the discharge cut-off voltage of 0.8V, and the cycle of different current densities for 5 weeks. Record the specific capacity, voltage and other data of each cycle;
[0097] (2) Test the cycle performance at a current density of 0.4A / g. The specific test method is to clamp the button battery to the Xinwei battery tester, detect that the battery is normal and has no short circuit phenomenon, and then set the parameters on the BTS client on the control computer. The set parameters include the mass of the active material, the test current density of 0.4A / g, the charge cut-off voltage of 1.8V, the discharge cut-off voltage of 0.8V, and the number of cycles of 500. Record the specific capacity after the first and 500th cycles, and calculate the capacity retention rate of the battery.
[0098] The test results are as follows:
[0099] Table 1 Performance test results of button batteries prepared in Examples 5-8
[0100]
[0101] In the present invention, the conductive polymer-coated manganese dioxide nanowires are obtained by coating the surface of the manganese dioxide nanowires with a conductive polymer as a coating material, and then the battery prepared by using the conductive polymer-coated manganese dioxide nanowires as a positive electrode material has a higher specific capacity at different current densities and a higher capacity retention rate.
[0102] The possible reason is that manganese dioxide itself acts as an oxidant to initiate the polymerization reaction of conductive polymer monomers on the surface of manganese dioxide nanowires. A conformal coating is formed on the surface of manganese dioxide nanowires through a one-step reaction, which can reduce the products of self-polymerization of conductive polymers. Conductive polymers can only be polymerized on the surface of manganese dioxide nanowires to form a conformal coating. The binding force between the conformal coating and the manganese dioxide nanowires is stronger. Manganese dioxide itself acts as an oxidant to self-initiate without the need to add additional oxidants. The reaction conditions are mild, which ensures the initial nanowire morphology of manganese dioxide nanowires. The coated conductive polymer layer can effectively stabilize the structure of manganese dioxide nanowires, thereby ensuring the conductivity of the inner layer manganese dioxide nanowires and improving the cyclic stability of manganese dioxide nanowires coated with conductive polymers. At the same time, conductive polymers can also improve the electronic conductivity of manganese dioxide nanowires.
[0103] In addition, the conformal coating of the conductive polymer realizes the introduction of oxygen vacancies, which can improve the transmission of electrons in the manganese dioxide nanowires coated with the conductive polymer. On the basis of improving the conductivity of the conductive polymer, the conductivity of the manganese dioxide nanowires coated with the conductive polymer is further improved, thereby improving the rate performance of the manganese dioxide nanowires coated with the conductive polymer. The above reasons together make the inner and outer layers of the manganese dioxide nanowires coated with the polymer have excellent conductivity and a stable structure, so that the prepared battery has high cycle stability and rate performance.
[0104] Among them, in Example 5, the manganese dioxide nanowire coated with a conductive polymer prepared by using 3,4-ethylenedioxythiophene monomer as the conductive polymer monomer as the positive electrode of the battery has a better effect than the manganese dioxide nanowire coated with a conductive polymer prepared by using pyrrole monomer and aniline monomer as the conductive polymer monomer as the positive electrode of the battery in Examples 6 and 7. In Example 8, the mass of the conductive polymer monomer and the manganese dioxide nanowire in the manganese dioxide nanowire coated with a conductive polymer as the positive electrode of the battery is greater than that in Example 5, but the specific capacity and capacity retention rate of the prepared battery at different current densities are lower than those in Example 5. It can be seen that the higher the content of the conductive polymer monomer, the higher the specific capacity of the prepared battery.
[0105] 2. The surface of the PEDOT-coated manganese dioxide nanowires prepared in Example 1 was scanned by a high-energy electron beam, and the SEM image was as follows: Figure 1 shown.
[0106] from Figure 1It can be seen that the aspect ratio of the PEDOT-coated manganese dioxide nanowires prepared in Example 1 exceeds 100, indicating that the PEDOT-coated manganese dioxide nanowires have a large specific surface area and abundant active sites, which can increase the reaction area between the material and zinc ions and improve the specific capacity of the material. It is proved that the in-situ coating of PEDOT initiated by manganese dioxide will not damage the nanowire structure of manganese dioxide, ensuring the initial nanowire morphology of manganese dioxide nanowires, and the coated conductive polymer layer can effectively stabilize the structure of manganese dioxide nanowires, thereby ensuring the conductivity of the inner layer manganese dioxide nanowires and improving the cycle stability of manganese dioxide nanowires coated with conductive polymers.
[0107] 3. Raman spectroscopy was used to test the manganese dioxide nanowires, PEDOT, and PEDOT-coated manganese dioxide nanowires in Example 5. The specific test method was to open the Raman tester and start the control software. The material was prepared into a powder and spread on a glass slide. The glass slide was placed on the sample stage of the Raman tester. The sample was focused through a microscope so that the laser beam could accurately irradiate the test area of the sample. The wavelength range of the test was set to 200-2000cm on the control computer. -1 , select a suitable laser source, set the integration time to 10 seconds, start spectrum collection, the software will automatically record the scattered light, and after the integration time is over, the software will generate a spectrum. The obtained Raman spectrum is as follows Figure 2 shown.
[0108] from Figure 2 It can be seen that the Raman spectrum of the PEDOT-coated manganese dioxide nanowires has both the Mn-O characteristic peak of manganese dioxide and the CC, Cα=Cβ, and C=C characteristic peaks of PEDOT, indicating that PEDOT is successfully coated on the surface of the manganese dioxide nanowires, and further proves that the in-situ coating of PEDOT initiated by manganese dioxide will not damage the structure of the manganese dioxide nanowires.
[0109] 4. Use paramagnetic resonance technology to obtain the electron paramagnetic resonance (EPR) spectra of the manganese dioxide nanowires and PEDOT-coated manganese dioxide nanowires in Example 5. The specific acquisition method is to turn on the ESR spectrometer, start the control software, load the sample into the ESR sample tube, and place the sample tube into the sample cavity in the magnetic field. Set the microwave frequency, usually in the range of 9-10 GHz. Set the magnetic field range, usually between 0.3-1.0 T (Tesla). Start the magnetic field scan, the magnetic field will gradually increase or decrease, and record the microwave absorption under different magnetic fields. The instrument will record the relationship between microwave absorption and magnetic field to form an ESR spectrum. The results are as follows: Figure 3 shown.
[0110] from Figure 3It can be seen from the EPR spectrum of the PEDOT-coated manganese dioxide nanowire that there is an obvious signal at g=2.003, while there is no signal peak in the EPR spectrum of the manganese dioxide nanowire. The existence of the signal peak indicates that there are oxygen vacancies in the PEDOT-coated manganese dioxide nanowire. The introduction of oxygen vacancies can improve the transmission of electrons in the manganese dioxide nanowire coated with the conductive polymer. On the basis of improving the conductivity of the conductive polymer, the conductivity of the manganese dioxide nanowire coated with the conductive polymer is further improved, thereby improving the rate performance of the manganese dioxide nanowire coated with the conductive polymer.
[0111] Comparative Example 1
[0112] A method for preparing a button battery, which is different from Example 5 in that the manganese dioxide nanowires are not coated with conductive polymer monomers, and the prepared manganese dioxide nanowires are directly used as active materials to prepare the positive electrode of the zinc ion battery.
[0113] Comparative Example 2
[0114] A method for preparing a button battery, which differs from Example 5 in that an external oxidant is added to initiate the in-situ coating of a conductive polymer on manganese dioxide nanowires. In the step of preparing the manganese dioxide nanowires coated with a conductive polymer, 0.5 g of 3,4-ethylenedioxythiophene monomer is added and 2.0 g of an oxidant ferric chloride is added at the same time. Ultrasonic dispersion and high-speed stirring are performed. After the polymerization reaction for 12 hours, the mixture is centrifuged and freeze-dried.
[0115] Comparative Example 3
[0116] A method for preparing a button battery, which differs from Example 5 in that, in the step of preparing manganese dioxide nanowires coated with a conductive polymer, the mass of the conductive polymer monomer 3,4-ethylenedioxythiophene monomer is 1 g, and the mass of the manganese dioxide nanowire is 10 g.
[0117] Comparative Example 4
[0118] A method for preparing a button battery, which differs from Example 5 in that in the step of preparing the manganese dioxide nanowires coated with a conductive polymer, the pH is adjusted to be greater than 4.
[0119] Comparative Example 5
[0120] A method for preparing a button battery, which differs from Example 5 in that, in the step of preparing manganese dioxide nanowires, 10 mmol of ammonium sulfate, 10 mmol of manganese sulfate, and 10 mmol of ammonium persulfate are added to 200 mL of deionized water, stirred until completely dissolved, and then transferred to a high-temperature reactor, and a hydrothermal reaction is carried out at 180° C. for 24 hours. At the same time, magnetic stirring is applied to the reaction solution. After the reaction is completed, centrifugation is carried out and drying is carried out to obtain manganese dioxide nanowires.
[0121] Comparative Example 6
[0122] A method for preparing a button battery, which differs from Example 5 in that, in the step of preparing manganese dioxide nanowires, 20 mmol of ammonium sulfate, 5 mmol of manganese sulfate, and 5 mmol of ammonium persulfate are added to 200 mL of deionized water, stirred until completely dissolved, and then transferred to a high-temperature reactor, and a hydrothermal reaction is carried out at 120° C. for 24 hours. At the same time, magnetic stirring is applied to the reaction solution. After the reaction is completed, centrifugation is carried out and drying is carried out to obtain manganese dioxide nanowires.
[0123] 1. The button batteries prepared in Comparative Examples 1-6 were tested for specific capacity at a current density of 0.1 A / g using the same method as in the example; the rate performance was tested at a current density of 5.0 A / g; the cycle performance was tested at a current density of 0.4 A / g, and the capacity retention rate of the battery was tested after 500 cycles.
[0124] The test results are as follows:
[0125]
[0126] In Comparative Example 1, the manganese dioxide nanowires were not coated with a conductive polymer monomer, and the prepared manganese dioxide nanowires were directly used as an active material to prepare a zinc ion battery positive electrode. The prepared button battery had a significantly reduced specific capacity and capacity retention at different current densities compared to the button battery prepared in Example 5. This may be because the prepared manganese dioxide nanowires were directly used as an active material to prepare a zinc ion battery positive electrode, and no conductive coating layer was formed on the surface of the manganese dioxide nanowires, resulting in poor conductivity.
[0127] In Comparative Example 2, 2.0 g of oxidant ferric chloride was additionally added as an oxidant to prepare a conductive polymer-coated manganese dioxide nanowire. The button battery assembled had a specific capacity and capacity retention at different current densities that were far inferior to those in Example 5, proving that the present invention can form a conformal coating on the surface of the manganese dioxide nanowire by a one-step method, which can reduce the product of self-polymerization of the conductive polymer. The conformal coating layer has a stronger binding force with the manganese dioxide nanowire. Manganese dioxide itself acts as an oxidant to self-initiate without the need to add additional oxidants. The reaction conditions are mild, ensuring the initial nanowire morphology of the manganese dioxide nanowire. The coated conductive polymer layer can effectively stabilize the structure of the manganese dioxide nanowire, thereby ensuring the conductivity of the inner layer manganese dioxide nanowire and improving the cycle stability of the manganese dioxide nanowire coated with the conductive polymer.
[0128] The conductive polymer-coated manganese dioxide nanowires prepared in Comparative Example 3 were used to assemble button batteries, and the specific capacity and capacity retention rate at different current densities were not as good as those of the button batteries in Example 5. It can be seen that when the conductive polymer-coated manganese dioxide nanowires are used, the effect of improving the conductivity is limited when the polymer monomer content is too small. As the polymer monomer content gradually increases, the conductivity shows a trend of first increasing and then decreasing. Too high a polymer monomer content not only leads to an increase in cost, but also when the ratio with the manganese dioxide nanowire exceeds 1:1, the conductivity begins to show a decreasing trend.
[0129] In the step of preparing manganese dioxide nanowires in Comparative Example 4, the pH is greater than 4, and the obtained conductive polymer-coated manganese dioxide nanowires are used to assemble button batteries. The specific capacity and capacity retention rate at different current densities are not as good as the button batteries in Example 5, and the capacity retention rate is much lower than that in Example 5. It can be seen that the pH value in the step of preparing manganese dioxide nanowires has a great influence on the reaction results, and both too high and too low pH are not conducive to the formation of a stable polymer coating on the surface of the manganese dioxide nanowires.
[0130] In the step of preparing manganese dioxide nanowires in Comparative Example 5, the ratio of ammonium sulfate, manganese sulfate and ammonium persulfate is 1:1:1. The obtained conductive polymer-coated manganese dioxide nanowires are used to assemble button batteries. The specific capacity and capacity retention rate at different current densities are not as good as those of the button batteries in Example 5. This may be because the ratio of ammonium sulfate, manganese sulfate and ammonium persulfate affects the structure of the generated manganese dioxide nanowires, resulting in differences in the conductivity of the manganese dioxide nanowires.
[0131] In the step of preparing manganese dioxide nanowires in Comparative Example 6, a hydrothermal reaction was carried out at 120°C for 24 hours. The obtained conductive polymer-coated manganese dioxide nanowires were used to assemble button batteries. The specific capacity and capacity retention rate at different current densities were not as good as those of the button batteries in Example 5. It can be seen that a too low hydrothermal reaction temperature has a great influence on the structure of manganese dioxide nanowires, and also leads to differences in the conductivity of manganese dioxide nanowires.
[0132] 2. Obtain the rate performance curves of the button batteries prepared in Example 5 and Comparative Example 1 at different current densities. The specific acquisition method is to clamp the button batteries of Example 5 and Comparative Example 1 onto the Xinwei battery tester, detect that the batteries are normal and have no short circuit, and then set the parameters on the BTS client on the control computer. The set parameters include the mass of the active material, the tested current density of 0.1, 0.2, 0.4, 0.8, 1.0, 1.5, 2.0, 3.0, 5.0A / g, the charge cut-off voltage of 1.8V, the discharge cut-off voltage of 0.8V, and 5 cycles of different current densities. Record the specific capacity, voltage and other data of each cycle, export the data and draw a graph through ORIGIN. The results are as follows: Figure 4 shown.
[0133] from Figure 4 It can be seen that the rate performance of the battery made of PEDOT-coated manganese dioxide nanowires in Example 5 is better than the rate performance of the button battery made of manganese dioxide nanowires directly as the positive electrode material in Comparative Example 1.
[0134] 3. Obtain the cycle performance curve of the button battery prepared in Example 5 and Comparative Example 1 at a current density of 0.4A / g for 500 cycles. The specific acquisition method is to clamp the button battery to the Xinwei battery tester, detect that the battery is normal and has no short circuit phenomenon, and then set the parameters on the BTS client on the control computer. The set parameters include the mass of the active material, the tested current density of 0.4A / g, the charge cut-off voltage of 1.8V, the discharge cut-off voltage of 0.8V, the number of cycles of 500, etc. Record the specific capacity of each cycle battery, export the data after the test, and draw a graph through ORIGIN. The results are as follows: Figure 5 shown.
[0135] from Figure 5 It can be seen that the cycle stability of the battery prepared by PEDOT-coated manganese dioxide in Example 5 is better than the cycle stability of the battery prepared by directly using manganese dioxide nanowires as the battery positive electrode in Comparative Example 1.
[0136] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A battery positive electrode material, characterized in that: The invention comprises manganese dioxide nanowires and conductive polymers, wherein the conductive polymers are coated on the surfaces of the manganese dioxide nanowires.
2. The battery positive electrode material according to claim 1, characterized in that The battery positive electrode material has oxygen vacancies.
3. The battery positive electrode material according to claim 1, characterized in that The conductive polymer includes at least one of 3,4-ethylenedioxythiophene polymer, pyrrole polymer and aniline polymer.
4. The battery positive electrode material according to claim 1, characterized in that The manganese dioxide nanowires are prepared by hydrothermal reaction of ammonium sulfate, manganese sulfate and ammonium persulfate; Preferably, the molar ratio of ammonium sulfate, manganese sulfate and ammonium persulfate is 3-5:0.5-1.5:1; Preferably, the temperature of the hydrothermal reaction is 150-200° C., and the time of the hydrothermal reaction is 20-30 h.
5. A method for preparing a positive electrode material for a battery as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: The manganese dioxide nanowires are added into a dispersion solvent, the pH range is adjusted, a polymer monomer is added and mixed, and a polymerization reaction is carried out to obtain the manganese dioxide nanowires coated with a positive electrode material polymer.
6. The preparation method according to claim 5, characterized in that: The pH range is 2.5-4.5; Preferably, the pH range is 3-4.
7. The preparation method according to claim 5, characterized in that: The mass ratio of the manganese dioxide nanowire to the polymer monomer is 0.5-2.5:1; Preferably, the manganese dioxide nanowires and the polymer monomers are mixed in a mass ratio of 1-2:1; the polymer monomers include at least one of 3,4-ethylenedioxythiophene monomers, pyrrole monomers, and aniline monomers.
8. The preparation method according to claim 5, characterized in that: The manganese dioxide nanowires are prepared by hydrothermal reaction of ammonium sulfate, manganese sulfate and ammonium persulfate; Preferably, the molar ratio of ammonium sulfate, manganese sulfate and ammonium persulfate is 3-5:0.5-1.5:1; Preferably, the temperature of the hydrothermal reaction is 150-200° C., and the time of the hydrothermal reaction is 20-30 h.
9. A battery, characterized in that: The invention comprises the battery positive electrode material according to any one of claims 1 to 4 or the positive electrode material prepared by the preparation method according to any one of claims 5 to 8.
10. The method for preparing a battery according to claim 9, characterized in that: The following steps are involved: S1. Prepare a positive electrode for a battery: add the positive electrode material for a battery according to any one of claims 1 to 4 or the positive electrode material prepared by the preparation method according to any one of claims 5 to 8 to N-methylpyrrolidone, mix into a uniform slurry, and coat the slurry on a titanium foil to prepare a positive electrode for a zinc ion battery; S2. Prepare the battery: Use metal zinc sheet as the negative electrode, glass fiber as the separator, and zinc sulfate as the electrolyte to assemble into a button battery; Preferably, the mass ratio of the positive electrode material, acetylene black and polyvinylidene fluoride is 5-10:0.5-2:1; Preferably, the solid content of the slurry is 55% to 60%.
Citation Information
Patent Citations
Preparation method of nanostructured polypyrrole
CN102924718A
High-specific-capacitance manganese-dioxide conducting polymer composite electrode material with core-shell structure and manufacturing method thereof
CN103151179A
Rodlike manganese dioxide / polyaniline composite material as well as preparation method and application of rodlike manganese dioxide
CN106684331A
Preparation method and application of lattice defect-containing superfine MnO2 nanowire
CN113044886A
Oxygen vacancy manganese dioxide / graphene oxide aqueous zinc ion positive electrode material and preparation method thereof
CN115842124A